Development of implanted drug delivery micropump - Wang, Xiaodong. (2008)
This thesis aims to develop a new micropump for implanted drug delivery in the human body, which may have the following features- simple structure; possibility f using bio-friendly material; large flow rate and backpressure; and miniaturiability.